Integration of negative experiences: A neuropsychological framework for human resilience. (2nd September 2015) - Quirin, Markus; Kent, Martha; Boksem, Maarten A. S.; Tops, Mattie
Abstract: We propose that the fundamental mechanism underlying resilience is the integration of novel or negative experiences into internal schemata. This process requires a switch from reactive to predictive control modes, from the brain's salience network to the default mode network. Reappraisal, among other mechanisms, is suggested to facilitate this process.